Process Parameters Optimization of High Density Polyethylene (HDPE) Friction Stir Welded Plates - Mazlan, Mohamad Mizal Saiful Anuar (IRC, 2016)
This thesis resembles the study on how to achieve an optimum process parameter of Friction Stir Welding (FSW) technique on polymeric materials. The FSW techniques was firstly founded in 1991 by Wayne Thomas at TWI, United Kingdom. FSW technique is the combination between frictional and stirring movements between two surfaces in contact to each other which produce the heat generation. Recently, the application of FSW technique also have been widely used for polymeric materials such as HDPE. Then, the FSW technique have an ability to weld the HDPE into complex and larger shape suitable with industry requirements. In this study, the motivation comes from the uses of plastic materials in one of the component in oil and gas tools which are known as Seismic Underground Cable.